Cloning and analysis of human gastric mucin cDNA reveals two types of conserved cysteine-rich domains. - Klomp, L W (1995)
Human gastric mucin was isolated by successive CsCl-gradient ultracentrifugation in the presence of guanidinium hydrochloride to prevent degradation of the polypeptide moieties of the molecules. The amino acid sequence of a tryptic fragment of this molecule was identical to that of a tryptic fragment of tracheobronchial mucin. An oligonucleotide based on this sequence hybridized specifically to human stomach mRNA and was subsequently used to screen a human stomach lambda ZAPII cDNA library. The largest of 10 positive clones encoded 850 amino acid residues, including the tryptic fragment, with high amounts of threonine, serine and proline residues. Interestingly, cysteine accounted for almost 8% of the amino acid residues. The 3' part of the sequence was very similar but not identical to the 3' region of human tracheobronchial cDNA. No tandem repeated sequences were present and the deduced polypeptide sequence contained two potential N-linked glycosylation sites. Four cysteine-rich clusters were detected, one of which was apparently homologous to the D-domains present in other mucins and in von Willebrand factor. The arrangement of the cysteines in three other cysteine-rich clusters was conserved in the human gastric mucin cDNA in a similar fashion as in two domains in the MUC2 gene product. The cysteine-rich domains were separated by short stretches of non-repetitive amino acid residues with a very high content of threonine and serine residues. These data suggest that the encoded polypeptide of this clone may be involved in disulphide-bond-mediated oligomerization of the mucin, and provide new insights into the molecular organization of mammalian apomucins.